2011
DOI: 10.2460/javma.239.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of outcomes in dogs with periarticular and nonperiarticular histiocytic sarcoma

Abstract: Histiocytic sarcoma is a round-cell neoplasm associated with a poor prognosis in dogs. Advances in veterinary pathology and immunohistochemical techniques have enabled identification of the putative cell of origin and have resulted in the reclassification of HS in dogs.1,2 Currently, there are 3 recognized clinical manifestations of HS. Hemophagocytic HS is thought to arise from macrophages of the splenic red pulp and bone marrow and is definitively diagnosed by positive CD18 and CD11d antibody immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 7 publications
2
91
0
Order By: Relevance
“…72 Early detection and treatment of articular HS is potentially curative, while disseminated HS has a worse prognosis. 5,34 However, articular HS is capable of widespread dissemination since histiocytes, especially those of the various DC lineages, are actively migratory cells. This is reflected in the median survival of dogs with articular HS and evidence of metastatic disease (about 5-8 months).…”
Section: Distinctive Histiocytic Sarcoma Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Early detection and treatment of articular HS is potentially curative, while disseminated HS has a worse prognosis. 5,34 However, articular HS is capable of widespread dissemination since histiocytes, especially those of the various DC lineages, are actively migratory cells. This is reflected in the median survival of dogs with articular HS and evidence of metastatic disease (about 5-8 months).…”
Section: Distinctive Histiocytic Sarcoma Syndromesmentioning
confidence: 99%
“…This is reflected in the median survival of dogs with articular HS and evidence of metastatic disease (about 5-8 months). 18,34 Articular HS has a distinctive appearance: it occurs as multiple tan nodules located beneath the synovial lining. Hence, these lesions begin outside of the synovial space either within the joint and/or in a periarticular location.…”
Section: Distinctive Histiocytic Sarcoma Syndromesmentioning
confidence: 99%
“…Dogs with HS (hereafter referred to as HS dogs) exhibit generally poor treatment outcomes because of the tumor's aggressive biological behavior, including its high cell proliferation, multidrug resistance, and metastatic potential (Yamazaki et al, 2013(Yamazaki et al, , 2014. Lomustine (CCNU) or doxorubicin have been commonly used as antitumor agents for HS dogs (Rassnick et al, 2010); however, the therapeutic benefit on the disseminated and hemophagocytic HS is insufficient because of resistance to these drugs (Klahn et al, 2011;Rassnick et al, 2010). It is suggested that overexpression of the inhibitor of apoptosis protein (IAP) and P-glycoprotein (P-gp) is able to induce multidrug resistance in breast cancer cells and its chemoresistant cells (Liu et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Prognosis depends on the location of primary lesions: splenic HS commonly shows poor prognosis, whereas periarticular HS shows a better prognosis compared with non-periarticular HS (Klahn et al, 2011). We have shown that non-periarticular HS dogs exhibited significantly higher survivin expression, shorter DFI and ST as compared with other periarticular HS.…”
Section: Discussionmentioning
confidence: 73%
“…Response to CCNU was assessed based on diagnostic imaging of the chest, abdomen, and each primary location according to previously reported procedures (Klahn et al, 2011) and classified as follows: (1) complete response (disappearance of all clinical signs and disease through to at least day 21); (2) partial response (>50% or <100% decreases through to at least day 21); (3) stable disease (≤50% decreases or <20% increases through to at least day 21), or (4) progressive disease (≥20% increases in tumor volume or the development of new neoplastic lesions or metastases).…”
Section: Disease Free Interval and Survival Time In Test Casesmentioning
confidence: 99%